2019
DOI: 10.21037/tcr.2019.10.24
|View full text |Cite
|
Sign up to set email alerts
|

Reduced RANBP9 expression is associated with poor prognosis in colorectal cancer patients

Abstract: Background: Colorectal cancer (CRC) is the third most common malignancy worldwide. RANBP9 is a RAN-binding protein that has been reported to be a reliable predictor for prognosis in some human cancers. The mechanism of RANBP9 involvement in CRC carcinogenesis is unknown. This study measured RANBP9 expression levels in CRC to determine its association with clinicopathological parameters.Methods: This study included 228 CRC patients who underwent radical resection. RANBP9 expression was determined using immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Nowadays, the application of effective tumor biomarkers has become one of hot issues in the field of cancer research, and is associated with the patient’s quality of life and survival outcomes ( 12 , 13 ). THY1 has been identified over-expressed on the cytoplasmic membrane in several cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the application of effective tumor biomarkers has become one of hot issues in the field of cancer research, and is associated with the patient’s quality of life and survival outcomes ( 12 , 13 ). THY1 has been identified over-expressed on the cytoplasmic membrane in several cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven (11) of those entries were expected CTLH complex members, clearly indicating that the immunoprecipitation by 3xHA worked efficiently (Table 2). We repeated the same purging process for the V5-immunoprecipitated proteomic list in comparison with the three negative control groups (V5-immunoprecipitated from WT, Ig-immunoprecipitated from LysMBP9X mice, and Ig-immunoprecipitated from LysMBP9 WT controls).…”
Section: Ranbp9-v5 Can Be Efficiently Immunoprecipitated From Bp9v5 M...mentioning
confidence: 94%
“…While the absence of RanBP9 causes perinatal lethality, occasional RanBP9-deficient mouse survivors on a mixed genetic background display reduced body size and severe sterility both in males and females 7 . Expression of RanBP9 increases in several types of malignancies 1, [8][9][10][11] . Due to the weakening of DNA repair in RanBP9deficient cells, RanBP9 has been put forward as a potential target of therapy in nonsmall cell lung cancer 9,10,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified tumor size, clinical stage, and tumor indexes as the critical prognostic factors for colorectal cancer (2)(3)(4)(5). Lately, KPS, number of brain metastases, the albumin-to-globulin ratio, fibrinogen-toalbumin ratio and other hematological indicators are proved to related to overall survival in patients with colorectal cancer.…”
Section: Original Articlementioning
confidence: 99%